Paradox at play : metaphor in Meister Eckhart's sermons : with previously unpublished sermons - Johnson, Clint (Daniel Clinton); Eckhart, Meister, -1327 (The Catholic University Press, 2023)
"Fresh translations of Meister Eckhart's sermons are made available in this volume: three for the first time in English and sixteen others for the first time since C. de B. Evans translated them in 1924 and 1931, long before the critical editions of the manuscripts were published in 2003. Other important sermons are included in the translations as well. They are meant to improve upon previous translations through sensitivity to Eckhart's metaphorical repertoire and his subtle word choice and phrasing. The monograph portion of the volume describes Eckhart's metaphors and how they work together to form a cohesive whole. All of his homiletic choices are argued to be in service of the greater goal: catalyzing transformative change in his audience by insisting on his paradoxes and jarring people out of their customary way of relating to God and themselves"--